Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Pengangguran Dan Indeks Pembangunan Manusia Serta Inflasi Terhadap Tingkat Kemiskinan Di Kabupaten Malinau - Imanuel Jufri; Theresia Militina; Eny Rochaida (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The   purpose   of   this   research   was   to   analyze   the   effect   of   economic   growth, unemployment,  Human  Development  Index    (HDI),  and  inflation  on  poverty  rate  in  Malinau Regency.The secondary data analysis applying multiple linear regression to analyze the effect of four independent variables: economic growth (X1), unemployment (X2), Human Development Index (X3) and inflation (X4) on poverty rate (Y) as the dependent variable in Malinau Regency, North Kalimantan Province from 2004 to 2013.The result of F test analysis simultaneously showed that there was a significant effect of the independent varibles on the dependent variable. The regression coefficient of F-value was15.409  with  signficance  level  0.005  (    0.05).  This  indicated  that  the  model  analysis  was appropriately  used  in  this  research.  Furthermore,  T  test  for  the  partial  regression  found  thateconomic growth (X1) had a positively insignificant effect on poverty rate (Y). Meanwhile, the other two variables: unemployment (X2) and inflation (X4) showed a negatively insignificant effect on poverty rate (Y). Last but not least, Human Development Index (X3) had a negatively significant effect on poverty rate (Y).In conclusion, Human Development Index (HDI) is the most dominant variable affecting poverty rate in Malinau Regency, North Kalimantan Province. The Standardized Coefficients Beta of HDI is the greatest among the other variables.